PENINGKATAN KETERAMPILAN MENULIS TEKS EKSPLANASI DENGAN MENGGUNAKAN METODE STUDENTS TEAMS ACHIEVEMENT DIVISION (STAD) PADA SISWA KELAS XI IPA 3 UPT SMA NEGERI 2 BANTAENG - Nurul Amalia Saleh; Sitti Rabiah; Nurfathana Mazhud (STKIP Subang, 2023)
This study aims to determine the application of the STAD method to the learning outcomes of Indonesian language students in class XI SMA Negeri 2 Bantaeng and to determine the increase in learning outcomes in learning Indonesian in class XI SMA Negeri 2 Bantaeng This research is research in nature. Class actions carried out in cycles. Each cycle has four stages, namely the planning stage of observation and reflection. The subjects in the study were students of class XI IPA 3 UPT SMA Negeri 2 Bantaeng, which consisted of 32 students. Data collection was carried out by tests and nontes. In the process of the planning stages of cycle I and cycle II, the learning implementation plans are similar, what is different is the learning steps. The learning steps carried out in cycle I were not optimal because there were several learning steps that were not carried out properly and had an effect on the achievement of learning outcomes while in cycle II students were more enthusiastic in participating in the learning indicating that the application of the STAD method to Indonesian language learning outcomes in class XI students SMA Negeri 2 Bantaeng can succeed. The results of this study indicate that the process of implementing learning cycle I is not optimal, namely with a percentage result of 31% or with an average result of 71,48 different in cycle II which experiences more effective changes, namely with a percentage result of 88% or with an average result of 80,65. It can be concluded that the Application of the STAD Method in Improving the Explanatory Text Writing Skills of Class XI UPT SMA Negeri 2 Bantaeng was declared successful.